Critical perspectives on African genocide: memory, silence, and anti-Black political violence - Frankowski, Alfred; Ntihirageza, Jeanine; Eze, Chielozona (Postcolonial studies Genocide studies, 2021)
"This text explores critical perspectives on the intersections between colonialism, political violence, and environmentalism to deepen our understanding of genocide and genocidal violence"--